Challenges faced by Chinese firms implementing the ‘Belt and Road Initiative’: Evidence from three railway projects - Lingfei Weng (Elsevier, 2021)
In 2013, China launched its ‘Belt and Road Initiative’ (BRI) as a major effort to enhance international trade and economic development. An important feature of the BRI is that it supports free trade regimes and a world economy based upon open regional cooperation. The concept of BRI involves establishing a transport route between China and participating countries to provide more profitable trade and investment corridors. There are few comprehensive studies examining the social and environmental impact on development in recipient countries. To address this gap, this study gathered empirical evidence on railroad projects in three key countries: Indonesia, Ethiopia, and Kenya. The comparative analysis revealed that while political leaders signed agreements that welcomed China’s BRI in support of their national transport development plans, the implementation of these ambitious infrastructure projects faced significant management and operational challenges that had not been foreseen by the Chinese partners. More effective implementation of BRI infrastructure projects in the future will require better understandings of governance, specifically through harmonization with the cultural, institutional and political contexts in partner countries. Social and cultural characteristics of the countries where Chinese firms are working need to be well understood if sustainable and inclusive benefits from the BRI infrastructure projects are to be delivered. Further research on the benefits gained by local people living in the areas affected by the BRI investments is needed.